Maximizing the Versatility of Thin Flap from the Groin Area as a Workhorse Flap: The Selective Use of Superficial Circumflex Iliac Artery Perforator (SCIP) Free Flap and Superficial Inferior Epigastric Artery (SIEA) Free Flap with Precise Preoperative Planning - Kim, Hyung Bae; Min, Jae Chung; Pak, Changsik John; Hong, Joon Pio Jp; Suh, Hyunsuk Peter (Journal of Reconstructive Microsurgery, 2022)
Background This study aimed to evaluate the usefulness of the selective use of the superficial circumflex iliac artery perforator (SCIP) and the superficial inferior epigastric artery (SIEA) flap as a workhorse flap from the groin area with precise preoperative surgical planning.Methods A total of 79 free flap reconstructions were performed in the study period; 35 SCIP free flaps and 19 SIEA free flaps were performed in the study period. Detailed preoperative surgical planning was performed using computed tomography (CT) angiography and color Doppler ultrasound. Detailed anatomical information of the flaps and reconstructive outcomes were evaluated.Results Flap characteristics between SCIP free flaps and SIEA free flaps were similar. The average transverse distance of the perforator from anterior superior iliac spine was 15.91 cm in SCIP free flaps and 43.15 cm in SIEA free flaps. The overall flap success rate was 96.4%. Majority of the patients achieved satisfactory contour without debulking surgery. Donor site morbidity was minimal with one case of wound dehiscence.Conclusion The selective use of the SCIP and SIEA free flap in groin area is a safe and useful technique. The surgical outcomes were reliable and similar between the SCIP and SIEA free flaps. Preoperative vascular planning using CT angiography and color Doppler ultrasound is essential for selecting the proper flap.
Keywords: superficial circumflex iliac artery perforator; superficial inferior epigastric artery; preoperative vascular planning